Novel sweat-based wearable device for advanced monitoring of athletic physiological biometrics - Aguilar-Torán, J.; Rabost-Garcia, G.; Toinga-Villafuerte, S.; Álvarez-Carulla, A.; Colmena-Rubil, V.; Fajardo-Garcia, A.; Cardona-Bonet, A.; Casals-Terré, J.; Muñoz-Pascual, X.; Miribel-Català, P.; Punter-Villagrasa, J. (Sensors, 2023)
Blood testing has traditionally been the gold standard for the physiological analysis and monitoring of professional athletes. In recent years, blood testing has moved out of the laboratory thanks to portable handheld devices, such as lactate meters. However, despite its usefulness and widespread use, blood testing has several drawbacks and limitations, such as the need for the athlete to stop exercising for blood extraction and the inability to have data continuously collected. In this scenario, sweat has become an alternative to blood testing because of its rich content of electrolytes and metabolites, as well as small quantities of sugars, proteins, and ions. Nevertheless, there are few devices capable of analyzing this biofluid and providing useful information to users. In this paper, an electronic system designed for the autonomous analysis of sweat electrolytes and metabolites along with heart rate dynamics is presented. This system is part of a novel wearable device tailored for athletes that offers to the user a real-time assessment of their physiological status and performance.